Curse of the Spellmans [large type] - Lutz, Lisa (Lutz, Lisa. Spellman novel., 2008)
When Izzy Spellman, PI, is arrested for the fourth time in three months, she writes it off as a job hazard. She's been (obsessively) keeping surveillance on a suspicious next door neighbor (suspect's name: John Brown), convinced he's up to no good -- even if her parents (the management at Spellman Investigations) are not. When the (displeased) management refuses to bail Izzy out, it is Morty, Izzy's octogenarian lawyer, who comes to her rescue. But before he can build a defense, he has to know the facts. Over weak coffee and diner sandwiches, Izzy unveils the whole truth and nothing but the truth -- as only she, a thirty-year-old licensed professional, can. When not compiling Suspicious Behavior Reports on all her family members, staking out her neighbor, or trying to keep her sister, Rae, from stalking her "best friend," Inspector Henry Stone, Izzy has been busy attempting to apprehend the copycat vandal whose attacks on Mrs. Chandler's holiday lawn tableaux perfectly and eerily match a series of crimes from 1991-92, when Izzy and her best friend, Petra, happened to be at their most rebellious and delinquent. As Curse of the Spellmans unfolds, it's clear that Morty may be on retainer, but Izzy is still very much on the case...er, cases -- her own and that of every other Spellman family member.